IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI DALAM UJI MATERI PASAL 184 AYAT 4 UU NOMOR 27/2009 TENTANG MPR, DPR, DPD, DAN DPRD TERHADAP PROSEDUR PEMAKZULAN PRESIDEN DI INDONESIA - Kartiko, Galuh (JURNAL KONSTITUSI, 2011)
Constitution law court (MK) have granted application of cancellation of rights condition express opinion of DPR in attending 3 / 4 (three per four) from amount of member of DPR. Even so, this decision do not at moments notice water down the existence of impeachment to president of MK cancel section 184 sentence (4) UU 27 year 2009 about MPR, DPR, DPD, and DPRD arranging rule of conditions 3 / 4 quorum in plenary meeting of approval of rights suggestion express opinion. MK express that section opposes against UUD 1945 and do not have the power of law remains to. MK also consider that without going into effect it rule of section 184 sentence (4) UU 27 / 2009 this rule of conditions of decision making concerning suggestion usage of rights express opinion go into effect rule of simple majority. Member of DPR requests items test of UU. Interconnected Concept body politic in Indonesia in impeachment still weakens because tending to be influenced by political configuration. Therefore, rule of law have to be always strengthened, so that punish and constitution can be upheld without political intervention. Furthermore, state law concept in Indonesia has to always respect rule of law, which free from power intervention, and also importance of politics in straightening of law in every jurisdiction, including jurisdiction of MK.Â